BODY, GENDER AND SUBVERSION: INTERFACES BETWEEN PHILOSOPHY, LANGUAGE AND WITTGENSTEIN - Jonas Ribeiro , Magno (Revista Gênero e Interdisciplinaridade, 2023)
The present paper intends to show how the relationship between gender, body and its transdisciplinary problems occurs. Such conception is explored in the work to understand in which given gender inequality gained a linguistic legitimation in its existence, thus contributing to the submission and exclusion of women as an egalitarian presence to exist. For this, it was used as method of investigation the philosophy of the language to make such route in the history of the old philosophy. Also made use of Ludwig Wittgenstein’s philosophy of language, more precisely the concept of “language games” to better understand the relation and subversion of gender in the present day. And lastly, this course intends to think about the importance of women’s autonomy in their authentication of a body, the result of the origin of metaphors and the production of subjectivity.